Astrology and Western Society from the First World War to Covid-19
XX, 271 p.
Keywords: This book gathers contributions on the topic of astrology in the West during the twentieth and twenty-first centuries, from 1914–2022. It is the first collection exclusively devoted to a period that has been mostly neglected by historians of astrology, who have mostly devoted themselves to the ancient, medieval and early modern periods. Uninterested in vindicating or debunking astrology, contributors consider its cultural impact, its relation to historical events, and the ways in which it has changed in the last century. The broad range of subjects on modern Europe and the US include the relation of astrology with indigenous thought, interwar Polish astrology, and the relation of American astrologers to COVID. A bibliography of studies of modern astrology on a global basis is also included. This collection is a thoughtful contribution to the history of astrology and the sociology of belief as well as carrying significant implications for twentieth and twenty-first century history broadly. William Burns is a historian who lives in the Washington DC area. His interests include the history of science and the history of early modern and modern astrology. He has edited Astrology through History (2018), a reference book on the history of astrology and published articles on seventeenth-century astrology.